Sustainable urban development and its impact on facilities management: the case of the city of Doha, Qatar - Chipanga, Robert (Department of Construction Economics and Management, 2015)
This research study examines the extent of urban development in Doha in relation to the impact this development poses on Facilities Management (FM). The focus of this study is on the city of Doha, Qatar. Urban growth that is not underpinned by a sustainable development ethos presents unique challenges on social, economic, human and environmental development. Two fundamental drivers of the urban development, namely: the implementation of Qatar National Vision 2030 (QNV) and the preparation to host major sports events such as Men's Handball Tournament 2015 and FIFA Football World Cup in 2022 have been investigated. Particular emphasis is to be placed on the government to look beyond ambitions for creating a 'global hub city' and contextualise the position of Qatar in terms of limited population numbers, dependence on a foreign workforce and the hiring of knowledge instead of creating a base. The emergence of FM as an important dimension to sustainable development requires a paradigm shift in encouraging FM involvement in the development process. A case study was undertaken and a thematic analysis was adopted within a non-interventional interpretative paradigm. Field data were collected using semi-structured interviews with respondents being identified through convenience and purposeful sampling considerations. The data show that while the hosting of major sports events presents legacy issues and FM pressures after the events, it is the implementation of the QNV that also provided significant challenges on rapid urban growth, sustainable development and FM. Implications of the findings are that a national development strategy for an emerging economy is required to be underpinned by the application of a holistic and sustainable approach that provides social and economic development to the communities; the formulation of an urban development process that assists in creating a controlled urban growth that can offer a viable creation of social inclusivity needed to achieve sustainable development; and that the low level of FM expertise as a result of the limited number of FM firms and the lack of technology and techniques presents unique FM challenges in Qatar.